Satisfacción académica por la enseñanza virtual en estudiantes de medicina durante la pandemia Covid-19 - Llajaruna Ponce, Ronaldo (2023)
One of the measures adopted by the arrival of the COVID-19 pandemic was the change from face-to-face classes to virtual classes. Objective: To identify the level of academic satisfaction for virtual teaching in medical students during the COVID-19 pandemic in the period 2020-2021. Materials and methods: Cross-sectional descriptive study with a sample of 243 students from the first to the sixth year of the Faculty of Medicine of the National University of Trujillo enrolled in the academic period 2020-2021 to whom the Satisfaction Questionnaire for university students was applied towards online training (CSAUF) through Google Forms; For statistical analysis, the Kolmogorov-Smirnov and Mann-Whitney tests were used. Results: the students were moderately satisfied in 73.3% with a tendency to be very satisfied in 23.9%, only 2.9% were dissatisfied with virtual teaching and a non-significant difference (p ≥ .05) was evidenced in satisfaction. with virtual teaching among students of basic and clinical sciences. Conclusions: Medical students were moderately satisfied with virtual teaching and a non-significant difference was found between the satisfaction of basic and clinical science students.